Healthy diet and physical activity in schoolchildren aged 10-12 years - Alonso-Vargas, José Manuel; Melguizo-Ibáñez, Eduardo; Puertas-Molero, Pilar; Caracuel-Cáliz, Rafael (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Currently, obesity and overweight have become a very important problem throughout the society of developed countries. The increasing number of children who present obesity or weight problems can be influenced by the type of diet that they follow. The aim of this study was to analyse and compare the influence of the practice of physical activity and adherence to Mediterranean diet on the problem of obesity and focus on the differences regarding to gender. The study followed a descriptive, non-experimental design. It was carried out with the help of 346 schoolchildren from different schools from Granada who had to fill the KIDMED, PAQ-C and ad hoc questionnaires. As core results, it was found that boys show a greater adherence to Mediterranean diet and practice a higher level of physical activity than girls, but there is a bigger percentage of overweight boys. It was also found that there were statistically significant differences regarding to the relation of physical activity practice and Mediterranean diet adherence. As main conclusions, it is important to highlight that 5 out of 10 schoolchildren have a normal weight and almost half of the sample have a high adherence to Mediterranean diet.